Population structure and distribution of the endangered Vatica diospyroides in Southern Thailand to inform its conservation strategies - THEERA SRISAWAT; KATESARIN MANEENOON; PATTANA WUTTIPONG; SURAPHON THITITHANAKUL; JARASLAK PECHWANG; KHANCHAI WONGCHANA; PARINUCH CHUMKAEW; WARANYU RATCHAREON (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Srisawat T, Maneenoon K, Wuttipong P, Thitithanakul S, Pechwang J, Wongchana K, Chumkaew P, Ratchareon W. 2023. Population structure and distribution of the endangered Vatica diospyroides in Southern Thailand to inform its conservation strategies. Biodiversitas 24: 1493-1500. Vatica diospyroides Symington is an endemic and rare dipterocarp species. It is listed as Endangered under the IUCN Red List due to its decreasing population. It has been the subject of a wide range of medicinal studies, but there is no prior survey of its population. This study was conducted to investigate the population structure and distribution of V. diospyroides in the lowland Tapi River floodplain, Surat Thani, southern Thailand, covering in-situ (VAT01-VAT04) and ex-situ (VAT05-VAT06) areas. The total count method was employed over the entire studied area to assess the conservation status of V. diospyroides. The number and location of trees, height level and Circumference at Breast Height (CBH) were recorded and the relationship between plant height and CBH and evidence of threats were analyzed. In total 4,535 and 508 trees were recorded in the in-situ and ex-situ conservation areas, respectively. Height ranges of 1.1-5.0 m and 5.0-10.0 m were dominant among trees in the in-situ and ex-situ areas, respectively. Classes of 0-1.0 and 5.1-50.0 cm were the dominant CBH in the in-situ and ex-situ areas, respectively. The VAT03-VAT05 had normal stem growth pattern and scattered distribution with large trees classified by plant height and CBH. The population of V. diospyroides in the ex-situ conservation area were blended in vegetation within the protected area (VAT05) and a private area (VAT06). No threats were detected in the in-situ conservation area, except for the need to protect from humans, but management is necessary in the ex-situ area. This study has revealed the patterns of V. diospyroides composition and structure variations in southern Thailand to help species conservation and protection. The findings of this study imply that the conservation status and definite size of this tree species should be revised.